2020
DOI: 10.1016/j.ebiom.2020.102902
|View full text |Cite
|
Sign up to set email alerts
|

Real-time imaging of polymersome nanoparticles in zebrafish embryos engrafted with melanoma cancer cells: Localization, toxicity and treatment analysis

Abstract: Background The developing zebrafish is an emerging tool in nanomedicine, allowing non-invasive live imaging of the whole animal at higher resolution than is possible in the more commonly used mouse models. In addition, several transgenic fish lines are available endowed with selected cell types expressing fluorescent proteins; this allows nanoparticles to be visualized together with host cells. Methods Here, we introduce the zebrafish neural tube as a robust injection s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…Polymersomes are stable bilayer vesicular systems prepared from amphiphilic copolymers that resemble the structure of natural liposome [31]. Studies reported different polymerization techniques to synthesize amphiphilic copolymers such as ring-opening polymerization (ROP), atom transfer radical polymerization (ATRP), and reversible additionfragmentation chain transfer polymerization (RAFT) [31][32][33]. The amphiphilic nature of the block copolymers allows spontaneous self-assembly into high molecular weight aggregates.…”
Section: Polymersomementioning
confidence: 99%
See 1 more Smart Citation
“…Polymersomes are stable bilayer vesicular systems prepared from amphiphilic copolymers that resemble the structure of natural liposome [31]. Studies reported different polymerization techniques to synthesize amphiphilic copolymers such as ring-opening polymerization (ROP), atom transfer radical polymerization (ATRP), and reversible additionfragmentation chain transfer polymerization (RAFT) [31][32][33]. The amphiphilic nature of the block copolymers allows spontaneous self-assembly into high molecular weight aggregates.…”
Section: Polymersomementioning
confidence: 99%
“…Compared to other polymeric NPs, polymersomes offer several advantages: readily adjustable membrane permeability, efficient delivery of hydrophobic, and hydrophilic drugs due to the hydrophobic outer layer, tuneable physicochemical properties by manipulating the thickness of the membrane, and high stability [31][32][33][34]. Kocere et al [33] demonstrated the pH-responsiveness of their polyethylene glycol-block-poly (2-diisopropyl amino)ethyl methacrylate (PEG-PPDPA) polymersomes by releasing doxorubicin (DOX) only at low pH. They found that the cytotoxicity of DOX encapsulated in the polymersomes was reduced by 40-fold compared to the free DOX.…”
Section: Polymersomementioning
confidence: 99%
“…Using xenografts, with melanoma and kidney cancer cells, the PEG-liposomes showed a specific and rapid accumulation into the tumor and outside the vasculature after only 2–5 h post- injection (hpi) [ 72 ]. Kocere and colleagues demonstrated the selective accumulation of Cy5-labelled poly(ethylene glycol)-block-poly(2-(diisopropyl amino) ethyl methacrylate) (PEG-PDPA) NPs in TAMs using a melanoma xenograft model [ 137 ]. By injection of B6 mouse melanoma cells (labeled with GFP or RFP) in the neural tube of 3 dpf transgenic embryos ((Tg( fli1a :EGFP, Tg( mpeg1 :mcherry), Tg( mpx :GFP)) [ 33 , 119 , 153 ], they were able to observe tumor growth, angiogenesis, and accumulation of macrophages, but not neutrophils, within the tumor at 10 dpf.…”
Section: Preclinical Testing Of Nanoparticles Using Zebrafish Models Of Disease: Relevance Of Macrophagesmentioning
confidence: 99%
“…These DOX-loaded-PEG-PDPA NPs were i.v. injected in the melanoma model at 1 dpi, showing reduced toxicity, decreased proliferation, and increased apoptosis of cancer cells six days after treatment [ 137 ].…”
Section: Preclinical Testing Of Nanoparticles Using Zebrafish Models Of Disease: Relevance Of Macrophagesmentioning
confidence: 99%
“…The particles had been selectively accumulated at the neural tube cancer region and on some individual cancer cells and tumor-associated macrophages. And when doxorubicin was released from the particles a reduction in the systemic toxicity was seen compared to the toxicity of the free drug alone and a reduction in the cancer cell signal (less fluorescence signal) was seen after seven days of injection of the particles to the xenografted zebrafish [ 145 ] ( Table 1 ).…”
Section: Anti-cancer Nps Tested On Zebrafishmentioning
confidence: 99%